Trends and outcomes for non-elective neurosurgical procedures in Central Europe during the COVID-19 pandemic - Grassner, Lukas; Petr, Ondra; Warner, Freda M; Dedeciusova, Michaela; Mathis, Andrea Maria; Pinggera, Daniel; Gsellmann, Sina; Meiners, Laura C; Freigang, Sascha; Mokry, Michael; Resch, Alexandra; Kretschmer, Thomas; et al. (Scientific reports, 2021)
The world currently faces the novel severe acute respiratory syndrome coronavirus 2 pandemic. Little is known about the effects of a pandemic on non-elective neurosurgical practices, which have continued under modified conditions to reduce the spread of COVID-19. This knowledge might be critical for the ongoing second coronavirus wave and potential restrictions on health care. We aimed to determine the incidence and 30-day mortality rate of various non-elective neurosurgical procedures during the COVID-19 pandemic. A retrospective, multi-centre observational cohort study among neurosurgical centres within Austria, the Czech Republic, and Switzerland was performed. Incidence of neurosurgical emergencies and related 30-day mortality rates were determined for a period reflecting the peak pandemic of the first wave in all participating countries (i.e. March 16th-April 15th, 2020), and compared to the same period in prior years (2017, 2018, and 2019). A total of 4,752 emergency neurosurgical cases were reviewed over a 4-year period. In 2020, during the COVID-19 pandemic, there was a general decline in the incidence of non-elective neurosurgical cases, which was driven by a reduced number of traumatic brain injuries, spine conditions, and chronic subdural hematomas. Thirty-day mortality did not significantly increase overall or for any of the conditions examined during the peak of the pandemic. The neurosurgical community in these three European countries observed a decrease in the incidence of some neurosurgical emergencies with 30-day mortality rates comparable to previous years (2017-2019). Lower incidence of neurosurgical cases is likely related to restrictions placed on mobility within countries, but may also involve delayed patient presentation.
Keywords: pandemie; Infant; dospělí; COVID-19; neurochirurgie; senioři nad 80 let; předškolní dítě; retrospektivní studie; Humans; Neurosurgery; lidé středního věku; Middle Aged; Aged, 80 and over; Young Adult; Europe; mladý dospělý; mužské pohlaví; Child, Preschool; Adult; neurochirurgické výkony; Adolescent; Infant, Newborn; Evropa; novorozenec; ženské pohlaví; Neurosurgical Procedures; lidé; mladiství; Pandemics; dítě; Child; Aged; senioři; Male; Retrospective Studies; kojenec; Female